Agrotourism as an Educational Medium in Agricultural Education for Students in Bali - Putu Eka Wirawan; Ni Wayan Mega Sari Apri Yani (Institut Pariwisata dan Bisnis Internasional, 2026)
The rapid growth of tourism in Bali has strengthened the economy but has also marginalized the agricultural sector, reducing youth interest in agriculture and threatening its sustainability. Educational agrotourism has emerged as an innovative approach that integrates agriculture, tourism, and education through experiential learning. This study aims to analyze the role of agrotourism as a medium for agricultural education for students in Bali and to identify strategies for its effective and sustainable development. Using a descriptive qualitative approach, the research was conducted at selected agrotourism sites in Bali through in-depth interviews, participant observation, and documentation. The findings show that hands-on activities such as planting, harvesting, and interaction with farmers enhance students’ engagement, understanding of agricultural concepts, and positive attitudes toward agriculture and environmental sustainability. However, limited pedagogical capacity, lack of standardized learning modules, and weak integration with formal education remain major challenges. Therefore, integrated strategies involving pedagogical training, curriculum alignment, sustainable tourism principles, and cross-sectoral collaboration are essential.